PENGARUH VARIASI ELEKTRODA TERHADAP KELISTRIKAN SARI KULIT NENAS (ANANAS COMOSUS) SEBAGAI BIOBATERAI - Rahmasari Pohan; Masthura Masthura; Abdul Halim Daulay (JISTech (Journal of Islamic Science and Technology), 2021)
The need for an electrical energy source is currently a very necessary thing, therefore researchers conducted experiments on the use of pineapple peel (ananas  comosus) extract as an electrolyte solution with a variety of electrodes. This research was conducted with the aim of generating voltage, electric current, and strength values. The measure of the holding capacity of the solution used were 50 ml, 100 ml, 150 ml, 200 ml, and 250 ml. The electrodes to be used are in the form of copper-zinc, copper-iron, and copper-aluminum pairs with each plate measurement of 4 cm × 7 cm, thickness of 0.2 mm. To determine the magnitude of the value of the voltage and current, a resistance is given in the form of an LED lamp. Based on the results of the research the pH measurement of the solution was 3.9. The test results obtained by the pair of Cu:Zn plates are the best compared to other pairs of plates, namely by producing a voltage of 1.59 Volts, a current of 0.28 mA, and an strength values of 0.44 mW with a volume of 250 ml. This is due to the influence of the volume of the solution and the electrodes used, that the more plates submerged in the solution, the greater the energy produced.